The Role of Myeloid Cell Activation and Arginine Metabolism in the Pathogenesis of Virus-Induced Diseases - Burrack, Kristina S.; Morrison, Thomas E. (Frontiers in Immunology, 2014)
When an antiviral immune response is generated, a balance must be reached between two opposing pathways: the production of proinflammatory and cytotoxic effectors that drive a robust antiviral immune response to control the infection and regulators that function to limit or blunt an excessive immune response to minimize immune-mediated pathology and repair tissue damage. Myeloid cells, including monocytes and macrophages, play an important role in this balance, particularly through the activities of the arginine-hydrolyzing enzymes nitric oxide synthase 2 (Nos2; iNOS) and arginase 1 (Arg1). Nitric oxide (NO) production by iNOS is an important proinflammatory mediator, whereas Arg1-expressing macrophages contribute to the resolution of inflammation and wound repair. In the context of viral infections, expression of these enzymes can result in a variety of outcomes for the host. NO has direct antiviral properties against some viruses, whereas during other virus infections NO can mediate immunopathology and/or inhibit the antiviral immune response to promote chronic infection. Arg1 activity has important wound healing functions but can also inhibit the antiviral immune response during some viral infections. Thus, depending on the specific virus and the tissue(s) involved, the activity of both of these arginine-hydrolyzing enzymes can either exacerbate or limit the severity of virus-induced disease. In this review, we will discuss a variety of viral infections, including HIV, SARS-CoV, LCMV, HCV, RSV, and others, where myeloid cells influence the control and clearance of the virus from the host, as well as the severity and resolution of tissue damage, via the activities of iNOS and/or Arg1. Clearly, monocyte/macrophage activation and arginine metabolism will continue to be important areas of investigation in the context of viral infections.